Piezoresponse, Mechanical, and Electrical Characteristics of Synthetic Spider Silk Nanofibers - Nader Shehata (Nanomaterials, 2018)
This work presents electrospun nanofibers from synthetic spider silk protein, and their application as both a mechanical vibration and humidity sensor. Spider silk solution was synthesized from minor ampullate silk protein (MaSp) and then electrospun into nanofibers with a mean diameter of less than 100 nm. Then, mechanical vibrations were detected through piezoelectric characteristics analysis using a piezo force microscope and a dynamic mechanical analyzer with a voltage probe. The piezoelectric coefficient (d33) was determined to be 3.62 pC/N. During humidity sensing, both mechanical and electric resistance properties of spider silk nanofibers were evaluated at varying high-level humidity, beyond a relative humidity of 70%. The mechanical characterizations of the nanofibers show promising results, with Young’s modulus and maximum strain of up to 4.32 MPa and 40.90%, respectively. One more interesting feature is the electric resistivity of the spider silk nanofibers, which were observed to be decaying with humidity over time, showing a cyclic effect in both the absence and presence of humidity due to the cyclic shrinkage/expansion of the protein chains. The synthesized nanocomposite can be useful for further biomedical applications, such as nerve cell regrowth and drug delivery.